The eclipse of 'elegant economy' : the impact of the Second World War on attitudes to personal finance in Britain - Cohen, Martin (Modern economic and social history series., 2012)
With concepts of 'austerity' very much in the news, this book takes a fresh look at attitudes to consumption, consumerism and personal finance in Britain during the middle decades of the twentieth century. It argues that the pre-War fear of debt and social disdain for conspicuous consumption was replaced during the 1940s and 1950s by widespread acceptance of a consumer society. As the financial woes of the 21st century force a reassessment of the sustainability of a consumer-based society, this book provides a timely reminder of how attitudes to personal finance are of greater significance to.